2014
DOI: 10.5812/hepatmon.20014
|View full text |Cite
|
Sign up to set email alerts
|

HBV Vaccination Status and Response to Hepatitis B Vaccine Among Iranian Dentists, Correlation With Risk Factors and Preventive Measures

Abstract: Background:Studies showed that HBV vaccination and consequent level of antibody are not completely adequate among dentists despite performance of highly exposure prone procedures.Objectives:The objectives of the study were to evaluate the levels of responsiveness to HBV vaccine and to determine the occupational factors associated among dental staff.Materials and Methods:In total, 1612 dental health care workers were recruited. The level of anti-HBs was tested using a commercially enzyme-linked immunosorbent as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 27 publications
4
17
1
1
Order By: Relevance
“…Moreover, no association was observed between seroconversion after three doses of vaccine and gender, as was shown in the research of Alavian et al 28 . However, associations of female gender with higher antibody titer values have been shown, as has been observed in previous studies 3,26 . The majority of studies have shown that a longer interval of time between the last dose of vaccine and undergoing the anti-HBs test leads to significant impact on the seroprotection indexes, with a better response being obtained when the seroconversion test was performed in up to 6 months after vaccination 2,26,28 .…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Moreover, no association was observed between seroconversion after three doses of vaccine and gender, as was shown in the research of Alavian et al 28 . However, associations of female gender with higher antibody titer values have been shown, as has been observed in previous studies 3,26 . The majority of studies have shown that a longer interval of time between the last dose of vaccine and undergoing the anti-HBs test leads to significant impact on the seroprotection indexes, with a better response being obtained when the seroconversion test was performed in up to 6 months after vaccination 2,26,28 .…”
Section: Discussionmentioning
confidence: 58%
“…However, associations of female gender with higher antibody titer values have been shown, as has been observed in previous studies 3,26 . The majority of studies have shown that a longer interval of time between the last dose of vaccine and undergoing the anti-HBs test leads to significant impact on the seroprotection indexes, with a better response being obtained when the seroconversion test was performed in up to 6 months after vaccination 2,26,28 . In a study with professionals, it was observed that individuals who received the third dose of vaccine less than 5 years ago had higher titers of antibodies than those who received the last dose longer than 5 years ago 26 .…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Essa problemática é embasada no referencial teórico sobre a necessidade da imunização contra o vírus VHB a partir da compreensão sobre as consequências à saúde desses profissionais que negligenciam a dose vacinal (MOMENI et al, 2014;KUMAR et al, 2015). A vacinação contra a hepatite B torna-se uma grande aliada na preservação da saúde do indivíduo, visto que é a forma mais eficaz de amplo acesso e cobertura populacional, principalmente daqueles que estão em contato direto com fluídos corporais, sangue e materiais cortantes (REZENDE et al, 2010).…”
Section: Introductionunclassified